The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1046/j.1365-2036.2003.01662.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral tacrolimus (FK 506) on steroid‐refractory moderate/severe ulcerative colitis

Abstract: Background: Steroid refractory ulcerative colitis is most commonly treated with intravenous ciclosporin to avoid colectomy. In search for an alternative drug that can be administered orally we investigated oral tacrolimus (FK 506) for this indication. Methods: Nine patients with active, moderate/severe steroid refractory UC were treated with oral tacrolimus with a daily dose of 0.15 mg/kg body weight. After patients had responded azathioprine was added for longterm immunosuppression. Results: All patients resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 33 publications
2
64
0
1
Order By: Relevance
“…Glucocorticoid (GC) treatment can be effective on ulcerative colitis (UC) [1] , however, in relapsed cases, the conditions are frequently refractory even when a high dosage of GC is administered [2,3] . It is well known that a long-term use of GC often causes serious side effects [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoid (GC) treatment can be effective on ulcerative colitis (UC) [1] , however, in relapsed cases, the conditions are frequently refractory even when a high dosage of GC is administered [2,3] . It is well known that a long-term use of GC often causes serious side effects [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the flow diagram which describes the reasons for citations exclusion. Finally, 22 studies (4)(5)(6)(9)(10)(11)(12)(13)(14)(15)(16)(17)(20)(21)(22)(23)(24)(25)28,30,32,33) that fulfilled eligibility criteria were included. Only two studies were randomized controlled trials (24,25) (Ogata 2006 and Ogata 2012); these were included for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning, according to what is observed from uncontrolled studies, the relatively high proportion of patients who would eventually require colectomy in spite of receiving tacrolimus (4,5,10,13,28,32) (Fellermann 2002, Hogenauer 2003, Baumgart 2006, Benson 2007, Yamamoto 2008, Schmidt 2013. As a consequence, it would seem like tacrolimus could delay the need for colectomy in a selected group of patients -those moderate-to-severe UC patients with prior failure to other therapeutic alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, several uncontrolled (9,14,15,17,19) and two placebo-controlled studies (13,18) have demonstrated that tacrolimus can induce remission in both adults (9, 13-15, 17, 18) and children (19). Another calcineurin inhibitor, CsA, is also highly active (60% to 80%) in patients with UC whose disease fails to respond to intravenous corticosteroid therapy (20).…”
Section: Discussionmentioning
confidence: 99%